Relationship between incubation temperature and egg size with heart hypoplasy in broiler chicks at hatching - Morita, Viviane de Souza [UNESP]; Boleli, Isabel Cristina [UNESP]; Oliveira, João Ademir [UNESP] (My University, 2012)
It was analyzed if the effects of continuous incubation temperature deviations during the second half on the development of body, organs and hematological respiratory and energetic parameters differ between male and female from 30- and 60-week-old breeder eggs. From day 13, Cobb eggs were exposed to 36°C, 37.5°C, or 39°C. At 3, 6, 12, 24, 48 and 72 h after this change in the temperature and at hatch, red cells count, hematocrit, hemoglobin, mean corpuscular volume, plasma glucose level and body, liver and heart weights were evaluated. Independent of incubation temperature, sexes and breeder ages, mean corpuscular volume decreased and the other variables increased during late incubation. In 30-week-old breeder eggs, body weights and erythrocytic parameters were not influenced by temperature but liver and heart weights decreased increasing incubation temperature and glucose level increased at 36 and 39°C. In 60-week-old breeder eggs, males were heavier at hatching with incubation at 36°C and females had smaller body weights with incubation at 39°C. In both sexes, liver weight decreased and glucose concentration was higher at 36 and 39°C and heart weights and erythrocytes parameters were not influenced by temperature. Independent of breeder age, hatchability was lower at 39°C. The data show that high temperature from day 13 of incubation reduced more intensively the hatching success and caused cardiac hypoplasia in chicks from 30-week-old breeder eggs only, revealing for the first time that the susceptibility for ascites syndrome, by reduced heart development at hatching, is associated to a relationship between incubation temperature and egg size. © Asian Network for Scientific Information, 2012.
Keywords: Cardiac weight; Erythrogram; Glucose; Incubation; Thermal stress